Photovoice and empowerment: evaluating the transformative potential of a participatory action research project - Kirsten Budig; Julia Diez; Paloma Conde; Marta Sastre; Mariano Hernán; Manuel Franco (BMC, 2018)
Abstract Background Photovoice is a visual research methodology with the intention to foster social change. Photovoice has been used to investigate change in empowerment in vulnerable communities, However, the individual experience of participants involved in Photovoice projects is seldom scrutinized. Our aim was to explore and describe the individual experiences of the female individuals who participated in a previous Photovoice project. We analyzed a change in the women's empowerment in terms of: 1) gain in knowledge and skills, 2) change in self-perception, and 3) access to and use of resources. Methods This qualitative study took place in the low-income District of Villaverde (Madrid, Spain), from January-June 2016. We conducted 10 semi-structured interviews with the female residents who had participated in the previous Photovoice project. We also collected field notes. We analyzed these data through a direct qualitative content analysis. The three outlined dimensions of empowerment provided guidance for the analysis of the results. Results We found positive changes in the three dimensions of empowerment: 1) participants acquired new knowledge and developed critical awareness of their community; 2) the social recognition participants received transformed their self-perception; and 3) the project allowed them to expand their social networks and to build new links with different actors (research partners, local decision makers, media and the wider public). Conclusions Photovoice projects entail the opportunity for empowering participants. Future research using Photovoice should assess the influence it has on participants' empowerment changes and how to sustain these individual and social changes.